Perlindungan Hukum Pelecehan Seksual Terhadap Streamer Aplikasi Live Streaming Melalui Platform Sosial Media - Melani Pratama Putri; Gusti Ngurah Parikesit Widiatedja; I Nyoman Sukandia (Jurnal Ragam Pengabdian, 2026)
The development of digital technology, particularly through live streaming platforms, has created a new, intense interaction space between streamers and audiences, but has also opened up opportunities for online sexual harassment. This study aims to analyze the legal protection of the mental health rights of victims of digital sexual violence, particularly streamers, and to evaluate the reconstruction of digital platforms' legal responsibilities in ensuring user safety. The study uses a normative legal method with a statutory approach, examining various regulations such as Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence and Law Number 17 of 2023 concerning Health. The results of the study indicate that sexual harassment in live streaming is not only a violation of criminal law but also has a significant impact on victims' mental health, such as anxiety, stress, and psychological trauma. Although regulations have recognized the right to protection and recovery for victims, their implementation still faces obstacles, such as difficulties in providing evidence due to the real-time nature of content and the suboptimal regulation of digital platform responsibility. Therefore, strengthening synergy between the state, platforms, and law enforcement is needed to create effective protection mechanisms oriented towards victim recovery. This research emphasizes the importance of a health law approach in addressing digital sexual violence as part of human rights protection in the era of technological disruption.